Exploring Thresholds in the Foundational Skills for Reading and Comprehension Outcomes in the Context of Postsecondary Readers. (January 2023) - Magliano, Joseph P.; Talwar, Amani; Feller, Daniel P.; Wang, Zuowei; O'Reilly, Tenaha; Sabatini, John
There is a range of reasons why college students may be underprepared to read, but one possibility is that some college students are below a threshold of proficiency in the component skills of reading. The presence of thresholds means that when students fall below that threshold, their proficiency in that component skill of reading is not sufficient for there to be a relationship with comprehension performance. The present study assessed (a) whether there were thresholds in proficiencies in foundational skills, (b) whether students falling below the thresholds were disproportionately in developmental literary programs (i.e., institutionally designated as underprepared), and (c) the implications of being below the thresholds on engaging in strategic processing during reading. College students were administered assessments of foundational literacy skills, text comprehension, and strategic processing of texts. The sample included students who were enrolled in developmental literacy programs and students who were not. Thresholds were found in the foundational skills associated with word-, sentence-, and discourse-level processing. Participants below these thresholds were represented disproportionately by students determined to be underprepared for college and assigned to developmental literacy programs. Finally, students falling below the thresholds demonstrated lower reading strategy scores than students above the threshold.